Influence of bisphosphonates on the behavior of osteoblasts seeded onto titanium discs - Basso, Fernanda G.; Pansani, Taisa N. [UNESP]; Cardoso, Lais M. [UNESP]; Hebling, Josimeri [UNESP]; Real, Rodrigo Paes Vila; Costa, Carlos Alberto de Souza [UNESP] (FapUNIFESP (SciELO), 2020)
Among other factors, types of bisphosphonates and treatment regimens seem to be strongly associated with the success or failure of installation of osseointegrated implants. This study investigated the influence of two bisphosphonates, sodium alendronate (SA) and zoledronic acid (ZA), on the metabolism of osteoblasts. Human osteoblasts (Saos-2) were seeded onto machined or acid-treated titanium discs previously placed on 24-well plates in complete culture medium. After 24 h, cells were exposed to bisphosphonates at 0.5, 1 or 5 μM for 24 h, 48 h or 7 days. The effects of SA and ZA on osteoblasts were assessed based on the adhesion of these cells to the titanium surfaces by direct fluorescence, cell viability, total protein and collagen synthesis. Alkaline phosphatase activity and mineral nodule deposition by these cells were also evaluated. Data were evaluated by ANOVA and Tukey tests (α=0.05). Decreased adhesion of cells to the titanium discs was observed when exposed to both bisphosphonates; however, this lack of cell adhesion was more evident for ZA-treated cells. In addition, the exposure of osteoblasts to ZA decreased the viability, ALP activity and mineral nodule deposition, which may be related to poor osseointegration after implant installation.
Keywords: Bisphosphonates; Implantology; Osseointegration; Osteoblasts